Nilai-Nilai Pendidikan Akhlak Perspektif M. Quraish Shihab Pada Buku “Yang Hilang Dari Kita Akhlak” - Faisal; Yusnaili Budianti; Azizah Hanum OK (Cetta: Jurnal Ilmu Pendidikan, 2023)
This study aims to analyze Quraish Shihab's perspective on the values of moral education in the book Hilang Dari Kita: Akhlak and its relevance to moral education in contemporary Islamic education. This study uses non-intractive qualitative research, namely content analysis in the character study approach. The data sources for this research are the books we have lost: morals written by Quraish Shihab as primary data, and journals and books related to the theme of this research as secondary data sources. The results of this study indicate that according to Quraish Shihab in his perspective on the values of moral education he concluded that there are four human potentials that must be maintained and educated in a balanced way, these potentials are the potential for knowledge, potential for anger, potential for lust and potential for justice. Then in forming the morals of Quraish Shihab concluded the method of habituation. Regarding moral education material, Quraish emphasizes the practice of basic Islamic values contained in the pillars of faith and the pillars of Islam. Regarding the relevance of Quraish Shihab's thoughts about the values of moral education to contemporary education, according to this researcher there is a lot of relevance, because Quraish lives in the present era, and is actively involved in social activities and social media so that with his broad insights he can contribute relevant and contemporary thinking.